Executive Information System For Decision Making In Radio Management In Indonesia - Wijaya, Fathi Melondre Putra; Haryono, Kholid (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The advancement of information technology has encouraged media organizations, including radio stations, to adopt data-driven approaches in decision-making. However, radio stations often lack well-managed and systematic data, resulting in underutilization of information to support decisions through visual insights. This study aims to design an Executive Information System (EIS) dashboard capable of presenting strategic information to radio management for understanding programming and listener behavior. The dashboard design employs the Prototyping method, adopting the Spiral model principles. This approach enables iterative and responsive development aligned with stakeholder needs. The design process involves identifying information requirements, creating visual prototypes, and validating the design through display and data readability evaluations. The resulting dashboard provides visual representations of listener demographics, popular broadcast programs, and time slots with the highest engagement levels. The dashboard is recognized for assisting radio management in formulating data-driven content and promotional strategies. Furthermore, this study highlights the effectiveness of the Prototyping method in producing adaptive, communicative, and business-relevant dashboard designs.